Changes of bolus properties and the triggering of swallowing in healthy humans. (4th February 2021) - Kochi, Izumi; Takei, Eri; Maeda, Rumiko; Ito, Kayoko; Magara, Jin; Tsujimura, Takanori; Kulvanich, Sirima; Inoue, Makoto
Abstract: There is wide variation in chewing behaviours, even among healthy humans. Further, the way in which humans determine swallowing initiation when chewing solid foods remains unclear. The current study sought to investigate how the bolus properties change over time during chewing, and to clarify which factors affect chewing and swallowing behaviours, including swallowing initiation, in healthy humans. Twenty‐four healthy volunteers were instructed to chew 8 g of steamed rice and spit it out at 50%, 100% and 150% of their own chewing duration, defined as the time of chewing from onset of the first chewing cycle to onset of the first swallow. Chewing and swallowing behaviours were monitored and determined by visual inspection of video recordings. The physical properties such as hardness, cohesiveness and adhesiveness as well as water content of the bolus were measured. In each subject, maximum bite force, tongue pressure and stimulated salivary flow rate were also measured. Hardness gradually decreased, and the cohesiveness and water content of the bolus did not change up to 50% of chewing duration, followed by a slight but significant increase. The adhesiveness of the bolus rapidly decreased at the beginning of chewing. Chewing duration was significantly related to stimulated salivary flow rate; greater salivary flow rate was associated with shorter chewing duration. Variation of chewing duration and swallowing initiation was not dependent on bolus properties during the chewing of steamed rice, but mainly depended on the surface lubrication of the bolus.